@stevesims,
The equation shown in the previous post was
x / 18 = 2 / x
Where the 18 is
10 + 8
Where the 10 is the 10 years that it takes for an object to move 8 LY at 80%c.
And 8 is the time it takes light to move 8 LY.
The 2 in the above equation is likewise 10 - 8
Where the 10 is the 10 years that it takes for an object to move 8 LY at 80%c.
And 8 is the time it takes light to move 8 LY.
The relevant formula is v = d/t, or rather t = d/v. Or, i.e. time = distance / velocity.
The 10, in generalized form is 8 LY (distance) / 80%c (velocity)
The 8, in generalized form is 8 LY (distance) / c (velocity)
If we now let d represent the 8 LY, and v represent 80%c, we can substitute:
x / 18 = 2 / x --- becomes
x / (10 + 8) = (10 - 8) / x --- becomes
x / (d/v + d/c) = (d/v - d/c) / x --- using words that would becomes
BettysTime / (distancebetweenEarthandStar/VelocityOfBettysShip + distancebetweenEarthandStar/VelocityOfLight) =
(distancebetweenEarthandStar/VelocityOfBettysShip - distancebetweenEarthandStar/VelocityOfLight) / BettysTime
Lets use t' (i.e. tPrime) instead of saying 'x' or 'BettysTime', and keep in mind that t would be AlicesTime (i.e. t without the Prime) and that t = d/v so long as we are using values from a single frame of reference.
t' / (d/v + d/c) = (d/v - d/c) / t'
If we cross multiply those fractions we get:
t'^2 = (d/v + d/c) (d/v - d/c)
Now on the right we get a common denominator by multiplying each fraction by 1, in the form c/c, or v/v.
t'^2 = (dc/vc + dv/vc) (dc/vc - dv/vc)
Each binomial factor on the right now has a common denominator, so we simplify:
t'^2 = ((dc+dv)/vc) ((dc-dv)/vc)
Now we multiply the binomials on the right:
t'^2 = (dc+dv) (dc-dv) / (vc)^2
t'^2 = ((dc)^2 +dvdc -dvdc -(dv)^2) / (vc)^2
t'^2 = ((dc)^2 - (dv)^2) / (vc)^2
t'^2 = (d^2c^2 - d^2v^2) / (v^2c^2)
Factor out the common d^2 in the numerator:
t'^2 = (d^2 (c^2 - v^2)) / v^2c^2
t'^2 = (d^2/v^2) ((c^2 - v^2)/c^2)
Now recall that t = d/v:
t'^2 = t^2 ((c^2 - v^2)/c^2)
Normalize the fraction:
t'^2 = t^2 ((c^2/c^2) - (v^2/c^2))
t'^2 = t^2 (1 - (v^2/c^2))
Divide by t^2:
t'^2 / t^2 = 1 - (v^2/c^2)
Take the square root of both sides:
t'/t = sqrt(1 - (v^2/c^2))
Take the reciprocal of both sides:
t/t' = 1 / sqrt(1-(v^2/c^2))
This last equation is the Lorentz factor (gamma), which can also be seen here:
https://en.wikipedia.org/wiki/Lorentz_factor in the "Definition" section on that page.